Beyond the norm: A case report on the unfolding spectrum of acute suppurative thyroiditis leading to abscess formation (Indian Journal of Case Reports, 2024)
The thyroid gland’s robust defenses, including a rich blood supply, lymphatic drainage, high iodine content, and physical isolation, typically render it resistant to infections. However, acute suppurative thyroiditis (AST) leading to a primary thyroid abscess is an uncommon occurrence, especially among children, accounting for only 0.1–0.7% of thyroid disorders. This case report outlines the clinical presentation of a 12-year-old male with prolonged fever, neck pain, sore throat, and swallowing difficulties. Staphylococcus aureus was identified as the causative agent. Treatment involved a combination of intravenous antibiotics and incision and drainage, resulting in a successful recovery. Despite its rarity, AST requires prompt recognition and intervention to prevent complications. This case emphasizes the significance of including AST in the differential diagnosis of neck swelling and underscores the necessity for early identification and appropriate management to ensure optimal patient outcomes.